Populisme et démocratie semi-directe : la dénaturation des procédés référendaires en France et aux Etats-Unis - Christophe Premat (Amnis)
If the feelings of frustration against the representative system are expressed by populism, it is crucial to question the link between a disappointment vis-à-vis the institutions and the semi-direct democracy instruments. By comparing France and United States in order to analyze on the one hand how popular initiatives and referenda influenced the legislation of some American States and on the other hand how national referenda in France were reduced to plebiscites, we wonder whether the nature of semi-direct democracy comes from the resentment against the slowness of the representative work or whether it deeply completes the transformation of representative government.